2017
DOI: 10.1038/s41559-017-0124
|View full text |Cite
|
Sign up to set email alerts
|

Gene flow from domesticated escapes alters the life history of wild Atlantic salmon

Abstract: Interbreeding between domesticated and wild animals occurs in several species. This gene flow has long been anticipated to induce genetic changes in life-history traits of wild populations, thereby influencing population dynamics and viability. Here, we show that individuals with high levels of introgression (domesticated ancestry) have altered age and size at maturation in 62 wild Atlantic salmon Salmo salar populations, including seven ancestral populations to breeding lines of the domesticated salmon. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
117
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(130 citation statements)
references
References 50 publications
9
117
2
2
Order By: Relevance
“…This is, however, in line with the previously reported finding that phenotypic F I G U R E 4 Estimated relationship between individual mass (g, lntransformed) of Atlantic salmon juveniles in semi-natural stream channels at the termination of the experiment and (a) family-level embryo mass (g, lntransformed), and (b) number of surviving juveniles in each stream channel plotted on raw data effects of farmed introgression vary among wild Atlantic salmon populations (Bolstad et al, 2017). Embryos of farmed males had significantly higher SMR than embryos of wild males in the crosses between farmed salmon and wild salmon of the Imsa population, but there was not a similar finding in the Surna population.…”
Section: Discussionsupporting
confidence: 87%
“…This is, however, in line with the previously reported finding that phenotypic F I G U R E 4 Estimated relationship between individual mass (g, lntransformed) of Atlantic salmon juveniles in semi-natural stream channels at the termination of the experiment and (a) family-level embryo mass (g, lntransformed), and (b) number of surviving juveniles in each stream channel plotted on raw data effects of farmed introgression vary among wild Atlantic salmon populations (Bolstad et al, 2017). Embryos of farmed males had significantly higher SMR than embryos of wild males in the crosses between farmed salmon and wild salmon of the Imsa population, but there was not a similar finding in the Surna population.…”
Section: Discussionsupporting
confidence: 87%
“…Others have concluded that growth differences between domesticated, hybrid, and wild salmon in the marine phase are not necessarily very clear, with small differences in maximum size at age but significant differences in minimum size at age (Jonsson & Jonsson, ). While the response in adult size in the IBSEM outputs reported here is low in comparison with the observations between domestication‐admixed and nonadmixed salmon (Figure vs. results by Bolstad et al., ), it is pertinent to point out that the model outputs here reflect the population average. We did not separate out domestication‐admixed and nonadmixed fish as was the case in the analysis by Bolstad and colleagues (Bolstad et al., ).…”
Section: Discussioncontrasting
confidence: 77%
“…While the response in adult size in the IBSEM outputs reported here is low in comparison with the observations between domestication‐admixed and nonadmixed salmon (Figure vs. results by Bolstad et al., ), it is pertinent to point out that the model outputs here reflect the population average. We did not separate out domestication‐admixed and nonadmixed fish as was the case in the analysis by Bolstad and colleagues (Bolstad et al., ). It is therefore suggested that the response revealed here is not necessarily very different to the observations made by Bolstad and colleagues, although this requires further investigation.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…; Bolstad et al. ), having perhaps reached some intermediate balance between migration and selection (as in Tufto ) prior to the cessation of introgression, the difference being the initial conditions.…”
Section: Model and Resultsmentioning
confidence: 99%